1992
DOI: 10.1016/0378-1097(92)90476-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of poly(3-hydroxybutyric acid) synthase genes of Rhodobacter sphaeroides and Rhodospirillum rubrum and heterologous expression in Alcaligenes eutrophus

Abstract: From genomic libraries of the purple non-sulfur bacteria Rhodospirillum rubrum Ha and Rhodobacter sphaeroides ATCC 17023 in the broad-host range cosmid pVK100, we cloned a 15- and a 14-kbp HindIII restriction fragment, respectively. Each of these fragments restored the ability to accumulate poly(3-hydroxybutyrate) (PHB), in the PHB-negative mutant Alcaligenes eutrophus PHB-4. These hybrid cosmids also complemented PHB-negative mutants derived from wild-type R. rubrum or R. sphaeroides. Both fragments hybridize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Previous studies identified and characterized two PHA polymerases (PhaCs) (5,12) in R. rubrum. Using these two sequences as the query, homology searches of the R. rubrum genome of strain ATCC 11170 revealed three genes encoding PHA polymerases, Rru_A0275, Rru_A2413, and Rru_A1816, which we designated phaC1, phaC2, and phaC3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified and characterized two PHA polymerases (PhaCs) (5,12) in R. rubrum. Using these two sequences as the query, homology searches of the R. rubrum genome of strain ATCC 11170 revealed three genes encoding PHA polymerases, Rru_A0275, Rru_A2413, and Rru_A1816, which we designated phaC1, phaC2, and phaC3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This metabolically versatile bacterium can grow under aerobic or anaerobic conditions or in the presence or absence of light, and in the latter condition it can use a variety of different carbon substrates (39,43). Previous studies and genome sequencing have revealed that R. rubrum can express three PHA polymerases (5,12). Because of its metabolic flexibility, R. rubrum offers the potential for converting many different carbon sources to PHA, and therefore there are considerable industrial interests in exploring this flexibility (6,35).…”
mentioning
confidence: 99%
“…Transgenic fibers were treated with Nile blue A fluorescent stain and examined at excitation wavelengths of 546 nm (21). PHB granules were also detected by transmission electron microscopy analysis (University of Wisconsin, Madison) (22). PHB was extracted and converted to crotonic acid and detected by HPLC (23).…”
Section: Methodsmentioning
confidence: 99%
“…7148) were examined by transmission electron microscopy, which has been used to visualize electron-lucent PHB granules in plants and in bacteria (9,22). This technique was also used to measure the size and location of PHB in fibers (Fig.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…Recently, the PHB-biosynthetic genes of nonsulfur purple bacteria were also cloned (Hustede et al, 1992). These bacterial polyesters have attracted much academic and industrial interest since they are thermoplastics, completely biodegradable and can be produced from renewable resources.…”
mentioning
confidence: 99%